Analysis of Queuing Theory at McDonald's Galuh Mas Karawang Using the Single Channel-Single Phase Model - Siti Nurrohmah; Agustian Suseno; Billy Nugraha (Fakultas Teknik, 2021)
Queue is the density or the number of customer waiting. However, the density of customers will also lead to the loss of potential customers. In this study, the aim of this research is to determine the queuing discipline applied by Mc Donald’s Galuh Mas Karawang and the characteristics of the queues needed to wait for the queue. Based on these problems, this study used is single channel-single phase model, where there is only one path for its service. The results showed that the queuing discipline used is First In First Out (FIFO) and the characteristics of the queue include average of 3 people queuing in the system, average queuing in the queue is 2 people, waiting time in system is 5.53 minutes, time expected by customers to wait in the queue is 4.183 minutes, with a server busy rate is 75,60% and a server unemployment rate is 24,40%.